Orthogonal basis of fractal functions for compression of images (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1996)
The aim of this paper is to build an orthogonal system in $L_{2}$, consisting of functions of a given fractal dimension. It is a tool for approximation of objects of certain fractal dimension. Here only the one-dimensional case is approached, however the considerations could be easily transferred to case of higher dimension.